IMPLEMENTASI PELAYANAN PUBLIK PEMERINTAH DAERAH: Studi tentang Penyelenggaraan Administrasi Terpadu Kecamatan (PATEN) di Kecamatan Gondang, Kabupaten Mojokerto Tahun 2019 - Nur Savitri, Ariva; Hasan Afandi, Ahmad; Rinayuhani, Tri Ratna (Universitas Islam Majapahit, Indonesia, 2023)
Quality public services are something that society needs. In order to create public services thatquality, the government issued Domestic Regulation Number 4 of 2010 concerning Guidelines for Integrated District Administration Services(PATENT). PATEN aims to improve service quality and bring services closer to the community. This research aims tounderstand the implementation of PATENTS in Gondang District and the factors that influence the implementation of PATENTS in Gondang District.This research uses descriptive qualitative research methods. The data in this research were obtained from interviews with informants, observations anddocument. This research uses a qualitative approach. The results of this research show that the implementation of PATEN in Gondang Districthas been running well but still has shortcomings in resource factors, namely the quantity and quality of staff and facilities. On factorscommunication, Gondang District has carried out transmission and provided understanding regarding PATENTS. From the disposition factors it can be seen thatThe staff understands their duties, has no resistance and behaves well when serving the community. So, it can be concluded thatThe inhibiting factor in PATENT implementation in Gondang District is resources. Driving factors for PATENT implementation inGondang District is communication and disposition